2016
DOI: 10.1007/s00439-016-1684-4
|View full text |Cite|
|
Sign up to set email alerts
|

IL8 gene as modifier of cystic fibrosis: unraveling the factors which influence clinical variability

Abstract: The severity of cystic fibrosis (CF) is associated with classes of mutations in the CFTR gene (cystic fibrosis transmembrane regulator), physical environment and modifier genes interaction. The IL8 gene (interleukin 8), according to its respective polymorphisms, influences inflammatory responses. This study analyzed IL8 gene polymorphisms (rs4073, rs2227306 and rs2227307), by means of PCR/RFLP, and their association with pulmonary function markers and clinical severity scores in 186 patients with CF, consideri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…The CF lung environment is dominated by neutrophils and elevated levels of the proinflammatory chemokine, IL-8 [ 41 ]. A recent study presented a genetic association of IL-8 polymorphisms with FEV 1 status of CF patients [ 42 ]. In our study, we observed increased expression of IL-8 transcripts in individuals with mild CF.…”
Section: Discussionmentioning
confidence: 99%
“…The CF lung environment is dominated by neutrophils and elevated levels of the proinflammatory chemokine, IL-8 [ 41 ]. A recent study presented a genetic association of IL-8 polymorphisms with FEV 1 status of CF patients [ 42 ]. In our study, we observed increased expression of IL-8 transcripts in individuals with mild CF.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, our research group has been working to contribute to studies on numerous genes, which can act on drug response, inflammatory processes and the immune response to the pathogens that aggravate, mainly, the pulmonary disease …”
Section: Introductionmentioning
confidence: 99%
“…Time to first P. aeruginosa airway infection, chronic P. aeruginosa infection, and mucoid P. aeruginosa have been associated with genetic variants in dynactin protein (DCTN4) (Emond et al 2012). P. aeruginosa mucoidy has been associated with pro-inflammatory cytokines interleukin 8 (IL-8) gene variants (Furlan et al 2016). However, even collectively, these human studies only partially explain the contribution of genetic variance to the risk of P. aeruginosa airway infection and should be validated in additional cohorts.…”
Section: Heterogenicity Of Human Populations Results In Different Resmentioning
confidence: 99%